If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6 = -15 Reorder the terms: 6 + 6x = -15 Solving 6 + 6x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = -15 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = -15 + -6 6x = -15 + -6 Combine like terms: -15 + -6 = -21 6x = -21 Divide each side by '6'. x = -3.5 Simplifying x = -3.5
| x^2-2x-1.1=0 | | -32-5x=4x+12 | | -3-4x=-9 | | 3x^2+15x+12= | | 7y+14=21x | | 10x-126=14x+35 | | -14-7x=-3 | | -5.5=-0.02x^2+x+0.5 | | -5.5=-0.02x+x+0.5 | | 5(n+7)=-44+2(n+6) | | y=-0.02x^2+x+0.5 | | 2x+7-3x=1 | | y=-0.02x+x+0.5 | | 3x+27=10x-33 | | -40=33x+15 | | 3=-x+1 | | 6(2x+1)-3(5x+2)=0 | | 8=8n-22-7n | | -x+3= | | y=-0.02x+x+6 | | 7=3(x-7)+10 | | 8x=16(x-36) | | x=-5+4 | | 3x+15=6x+7 | | 3(2-a)=8-a | | 3x-8=5(2x-3) | | 147-4x=23x+21 | | 5x=(6x-3) | | 5(2x-3)+6=43-3x | | 8+12x=15x-19 | | 2c+5=3c+7 | | 67-5x=9x+7 |